2022
DOI: 10.1186/s12891-022-05866-w
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent validity of DorsaVi wireless motion sensor system Version 6 and the Vicon motion analysis system during lifting

Abstract: Background Wearable sensor technology may allow accurate monitoring of spine movement outside a clinical setting. The concurrent validity of wearable sensors during multiplane tasks, such as lifting, is unknown. This study assessed DorsaVi Version 6 sensors for their concurrent validity with the Vicon motion analysis system for measuring lumbar flexion during lifting. Methods Twelve participants (nine with, and three without back pain) wore sensors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…Previously studies calculating peak ROM angles, in comparison to a gold standard, have reported limits of agreement ranging from -8.06 • to 5.67 • [25] and −3.86 • to 4.69 • [11]. Data from the current study showed similar but tighter limits of agreement (−1.65 • to 4.38 • ) prior to correction, and therefore it is possible that some of the range of these errors is due to sensor orientation, especially as no mention of orientation correction was made in these works.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previously studies calculating peak ROM angles, in comparison to a gold standard, have reported limits of agreement ranging from -8.06 • to 5.67 • [25] and −3.86 • to 4.69 • [11]. Data from the current study showed similar but tighter limits of agreement (−1.65 • to 4.38 • ) prior to correction, and therefore it is possible that some of the range of these errors is due to sensor orientation, especially as no mention of orientation correction was made in these works.…”
Section: Discussionmentioning
confidence: 97%
“…Despite this common use of accelerometers, it is not clear if initial sensor orientation angle has been considered in the quantification of the angles or ROM reported. For example, previously reported limits of agreement between gold standard methods and accelerometers, without correcting for initial orientation, range from -8.06 • to 5.67 • [25] and −3.86 • to 4.69 • [11], meaning that 95% of future paired observations are likely to fall between this range of error. These error ranges are large, and it is questionable as to whether this is a true reflection of the sensors' capabilities or a function of the initial sensor orientation as a source of error.…”
Section: Introductionmentioning
confidence: 99%
“…Kinematic data obtained from IMC systems have been validated in several studies in laboratories against data obtained from OMC systems [ 19 , 20 , 21 , 22 , 23 , 24 ]. Estimating kinetic variables such as backloading from IMC systems has also been validated in laboratories by using force platforms or instrumented shoes to measure the ground reaction forces [ 20 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%